2016
DOI: 10.7745/kjssf.2016.49.4.401
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 2-methylbutyric Acid as a Nematicidal Metabolite, and Biocontrol and Biofertilization Potentials of Bacillus pumilus L1

Abstract: The present study described the isolation of 2-methylbutyric acid (2-MBA) produced from Bacillus pumilus L1, to subsequently investigate its nematicidal activity for the control of the root-knot nematode. The results showed that 2-MBA could be purified by chromatographic techniques and was identified using nuclear magnetic resonance and liquid chromatography-mass spectrometry. Crude extract and partially purified compounds had a significant effect on the inhibition of egg hatchability and second-stage juvenile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…as biocontrol agents are promising, but their activity should be evaluated under field conditions. Lee et al (2016) reported that B. subtilis produced both protease and chitinase enzymes, which were the main causes for its root-knot nematode antagonistic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…as biocontrol agents are promising, but their activity should be evaluated under field conditions. Lee et al (2016) reported that B. subtilis produced both protease and chitinase enzymes, which were the main causes for its root-knot nematode antagonistic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…65 2-Methylbutyric acid (2-MBA) 145 was produced from Bacillus pumilus and was found to exhibit a dose-dependent effect on J2 mortality and egg-hatching ability for Meloidogyne arenaria . 66 …”
Section: Structures and Nematicidal Activitymentioning
confidence: 99%
“…This is an important precursor step for higherlevel identification (molecular formula and confirmed structure) (Schymanski et al, 2014), and relates to the main goal of metabolomics which is to identify a few unique chemical features that define a biological system (Worley & Powers, 2013). Higher-level identification has been achieved for some Bacillus nematicidal metabolites, including styrene produced by B. mycoides (Luo et al, 2018), 2-methylbutyric acid by B. pumilus L1 (Lee et al, 2016), uracil by B. cereus and B. subtilis, and dihydrouracil and 9H-purine by B. subtilis (Oliveira et al, 2014).…”
Section: The Influence Of Cultivation Media On Bacillus Metabolite Productionmentioning
confidence: 99%